How does it feel to be a problem? Patients' experiences of self‐management support in New Zealand and Canada. (22nd September 2018) - Sheridan, Nicolette F.; Kenealy, Timothy W.; Fitzgerald, Anita C.; Kuluski, Kerry; Dunham, Annette; McKillop, Ann M.; Peckham, Allie; Gill, Ashlinder
Abstract: Background: The impact of long‐term conditions is the "healthcare equivalent to climate change." People with long‐term conditions often feel they are a problem, a burden to themselves, their family and friends. Providers struggle to support patients to self‐manage. The Practical Reviews in Self‐Management Support (PRISMS) taxonomy lists what provider actions might support patient self‐management. Objective: To offer providers advice on how to support patient self‐management. Design: Semi‐structured interviews with 40 patient‐participants. Setting and participants: Three case studies of primary health‐care organizations in New Zealand and Canada serving diverse populations. Participants were older adults with long‐term conditions who needed support to live in the community. Main outcome measures: Qualitative description to classify patient narratives of self‐management support according to the PRISMS taxonomy with thematic analysis to explore how support was acceptable and effective. Results: Patients identified a relationship‐in‐action as the mechanism, the how by which providers supported them to self‐manage. When providers acted upon knowledge of patient lives and priorities, these patients were often willing to try activities or medications they had resisted in the past. Effective self‐management support saw PRISMS components delivered in patient‐specific combinations by individual providers or teams. Discussion and conclusions: Providers who establish relationships with patients can support them to self‐manage and improve health outcomes. Delivery of taxonomy components, in the absence of a relationship, is unlikely to be either acceptable or effective. Providers need to be aware that social determinants of health can constrain patients' options to self‐manage.